Selection and Evaluation of Electronic Resources - Doğan Atılgan; Yusuf Yalçın (Türk Kütüphaneciliği)
Publication boom and issues related to controlling and accession of printed sources have created some problems after World War II. Consequently, publishing industry has encountered the problem of finding possible solution for emerged situation. Industry of electronic publishing has started to improve with the rapid increase of the price of printed sources as well as the problem of publication boom. The first effects of electronic publishing were appeared on the academic and scholarly publications then electronic publishing became a crucial part of all types of publications. As a result of these developments, collection developments and service policies of information centers were also significantly changed. In this article, after a general introduction about selection and evaluation processes of electronic publications, the subscribed databases by a state and a privately owned university in Turkey and their usage were examined.